Fotografia e colagem na elaboração do pensamento artístico a partir da produção de Gê Viana - Ventura, Jessica Fernandes (2022)
Gê Viana is a visual artist from Maranhão, Brazil, who produces digital and/or analog collages by the junction of photographs, from her authorship, and/or images from archives. Her images challenge the Brazilian historicism, in them the artist develops fictional imagery narratives of dissident bodies inscriptions which suffered deletion and/or violence during the process of the Brazilian society formation. The aim of this work is to look to those images to comprehend how the photography and the collage act as mediation for the construction of her images. Based on the perspective of thinking inherent to the images, proposed by Etienne Samain, in order to observe how her images think. For that, the specificities of the photographic sign are contextualized from its ontology and from a brief history of the consolidation of photography as a means of expression, from this discussion the constructed character of the photographic image is located, which is used together with the collage as mediation for the narratives proposed by Gê Viana. Methodologically, the dissertation uses the artist’s images as a case study, in a detailed and guided reading by the reception of the images which are appreciated in their digital format. For the analysis of the images, the method of analysis proposed by Ana Maria Mauad is used and adapted, having a bibliographical review as a theoretical support for the understanding of these photographic images, which has its perceptual mediation in collage. As a result, it is expected to provide subsidies for a greater understanding of the image, particularly the photographic one, through an expanded reading of Gê Viana’s images, considering that the artistic practice provides support for the understanding of the social insertion of the images.